The Influence of Small Intestinal Bacterial Overgrowth in Digestive and Extra-Intestinal Disorders - Giuseppe Losurdo (International Journal of Molecular Sciences, 2020)
Small intestinal bacterial overgrowth (SIBO) is a condition hallmarked by an increase in the concentration of colonic-type bacteria in the small bowel. Watery diarrhea, bloating, abdominal pain and distension are the most common clinical manifestations. Additionally, malnutrition and vitamin (B12, D, A, and E) as well as minerals (iron and calcium) deficiency may be present. SIBO may mask or worsen the history of some diseases (celiac disease, irritable bowel disease), may be more common in some extra-intestinal disorders (scleroderma, obesity), or could even represent a pathogenetic link with some diseases, in which a perturbation of intestinal microbiota may be involved. On these bases, we performed a review to explore the multiple links between SIBO and digestive and extra-intestinal diseases.